Carbon intensity of global existing and future hydropower reservoirs. (July 2022) - Li, Mingxu; He, Nianpeng
Abstract: As the largest renewable electricity source, hydropower represents an alternative to fossil fuels to achieve a low-carbon future. However, increasing evidence suggests that hydropower reservoirs are an important source of biogenic greenhouse gases (GHGs), albeit with large uncertainties. Combining spatially resolved assessments of GHG fluxes and hydroelectric capacity databases, we assessed that global GHG emissions from reservoirs is 0.38 Pg CO2 eq.yr −1, accounting for 1.0% of global anthropogenic emissions. The median carbon intensity for hydropower is ∼63.0 kg CO2 eq. MWh −1, which is lower than that for fossil fuels, but higher than that for other renewable energy sources. High carbon intensity is mostly linked to shallow (water storage depth <20 m) and eutrophic reservoirs. Furthermore, we found that the reservoir carbon intensity (CI) value would be markedly increased to 131.5 kg CO2 eq. MWh −1 when considering the dams under construction and planning. A low-carbon future will benefit from optimal dam planning and management measures, i.e., applying sludge removal treatments, thereby reducing the proportion of shallow reservoirs and anthropogenic pollution. Highlights: GHG emissions from global reservoirs are ∼0.38 Pg CO2 eq.yr −1 . Half of hydropower reservoirs are incompatible with the low-carbon goal. High carbon intensity mostly occurred in shallow or trophic reservoirs.